The accuracy potential of Galileo E5/E1 pseudoranges for surveying and mapping - Colomina, Ismael; Miranda, Christian; Parés, M. Eulàlia; Andreotti, Marcus; Hill, Chris; Da Silva, Pedro F.; Silva, João S.; Monico, João F. Galera [UNESP]; Camargo, Paulo O. [UNESP]; Diez, José; Palomo, José Maria; Barbin, Silvio E.; et al. (My University, 2011)
In the paper we discuss the potential of the new Galileo signals for pseudorange based surveying and mapping in open areas under optimal reception conditions (open sky scenarios) and suboptimal ones (multipath created by moderate to thick tree coverage). The paper reviews the main features of the Galileo E5 AltBOC and E1 CBOC signals; describes the simulation strategy, models and algorithms to generate realistic E5 and E1 pseudoranges with and without multipath sources; describes the ionosphere modeling strategy, models and algorithms and discusses and presents the expected positioning accuracy and precision results. According to the simulations performed, pseudoranges can be extracted from the Galileo E5 AltBOC signals with tracking errors (1-σ level) ranging from 0.02 m (open sky scenarios) to 0.08 m (tree covered scenarios) whereas for the Galileo E1 CBOC signals the tracking errors range between 0.25 m to 2.00 m respectively. With these tracking errors and with the explicit estimation of the ionosphere parameters, simulations indicate real-time open sky cm-level horizontal positioning precisions and dm-level vertical ones and dm-level accuracies for both the horizontal and vertical position components.
Keywords: GALILEO; Galileo Signals; Ionosphere modeling; Ionosphere parameters; Optimal reception; Positioning accuracy; Positioning precision; Pseudorange; Simulation strategies; Tracking errors; Vertical positions; Algorithms; Computer simulation; Errors; Forestry; Ionosphere; Ionospheric measurement; Mathematical models; Surveys; Global positioning system; Mathematical Models; Simulation